Application of BASNEF Model to Predict Postpartum Physical Activity in Mothers Visiting Health Centers in Kermanshah - Zohreh Ouji; Majid Barati; Saeed Bashirian* (Hamadan University of Medical Sciences, 2014)
Background and Objectives: The high risk of physical inactivity in the postpartum period is associated with increased risk of obesity and diabetes in mothers. Therefore, the present study used the beliefs, attitudes, subjective norms, and enabling factors (BASNEF) model to identify the predictors of postpartum physical activity among women visiting health centers in Kermanshah (Western of Iran). Materials and Methods: This descriptive-analytical study was performed on 400 women who visited health centers in Kermanshah. Multistage sampling was adopted to select the participants. The subjects were asked to fill out a questionnaire containing demographic variables, the BASNEF model constructs, and a short form of the international physical activity questionnaire. Data were analyzed using logistic and linear regression analysis and Pearson's correlation analysis in SPSS-18. Results: Most mothers (83%) had low levels of physical activity. Knowledge, attitude, and subjective norms could significantly predict the intention to perform physical activity. These variables accounted for 21% of the variance in behavioral intention. Moreover, behavioral intention was the best predictor of postpartum physical activity behaviors (P<0.001 β = 0.140). Conclusion: Based on our findings, the majority of mothers were inactive during the postpartum period. Relevant interventions should thus be designed to modify mothers' behavioral intention and promote physical activity after childbirth.